The Economics of Renewable Energy Expansion in Rural Sub-Saharan Africa - Deichmann, Uwe; Meisner, Craig; Murray, Siobhan; Wheeler, David (2012)
Accelerating development in Sub-Saharan Africa will require massive expansion of access to electricity--currently reaching only about one third of households. This paper explores how essential economic development might be reconciled with the need to keep carbon emissions in check. We develop a geographically explicit framework and use spatial modeling and cost estimates from recent engineering studies to determine where stand-alone renewable energy generation is a cost effective alternative to centralized grid supply. Our results suggest that decentralized renewable energy will likely play an important role in expanding rural energy access. However, it will be the lowest cost option for a minority of households in Africa, even when likely cost reductions over the next 20 years are considered. Decentralized renewables are competitive mostly in remote and rural areas, while grid connected supply dominates denser areas where the majority of households reside. These findings underscore the need to decarbonize the fuel mix for centralized power generation as it expands in Africa.